The Study of Character and Narrative Function in The Fall of Gondolin by J.R.R Tolkien: A Narratology Criticism - roifah, miftahur; Sugiono, Erfin (LingPoet: Journal of Linguistics and Literary Research, 2024)
This study focuses on narratology in the novel The Fall of Gondolin by J.R.R. Tolkien, specifically exploring the character and narrative function. The main objective is to identify and analyze the development of the characters by identifying and analyzing the thirty-one narrative functions present in the story. The study adopts a qualitative descriptive method, using the narrative sections from The Fall of Gondolin as the data source. Through this approach, the author describes and explains the narrative functions and character types found in Tolkien's work. The findings of the study reveal fourteen narrative functions: absence, delivery, trickery, reconnaissance, wedding, departure, struggle, rescue, connective incident, beginning counteraction, guidance, receipt of magical agent, villainy, and six types of characters: hero, villain, princess, donor, helper, and dispatcher, as proposed by Vladimir Propp. The study's results demonstrate that the data related to narrative functions can be formulated and used to identify various character types, such as hero, princess, villain, helper, dispatcher, donor, and false hero. These character types can be analyzed by combining the collected data in accordance with the theoretical framework.